Kelayakan finansial usaha pengolahan terasi udang rebon di kelurahan Bontang Kuala kota Bontang provinsi Kalimantan Timur - Muhammad Syafril; Dayang Diah Fidhiani (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
The objectives of this study are a measure of the financial feasibility of The shrimp paste processing business, and to know the marketing chain study was conducted in the production center of The shrimp paste, Bontang Kuala Village. Sampling using the census method. There were 7 shrimp paste producers in the study area. Business feasibility of the financial aspect is measured by the analysis of discounted investment criteria; Net Present Value, Internal Rate of Return, Net Benefit-Cost Ratio, Payback period), and analysis of non-discount investment criteria; break-even point analysis and Return of Investment (ROI) analysis. Results showed that The shrimp paste processing business was financially feasible to be developed in the future, with NPV value were IDR. 32,667,112. IRR values respectively were 21%, Net B/C values were 2.1 and Payback period values were 3.3 years. The actual condition of shrimp paste processing business is above the break-even point condition for the aspect of sales and the production, Return of Investment (ROI) value were of 113.28%. Marketing channel patterns that occur are level 0 channel patterns, ie from producers to consumers.